Pengaruh Tingkat Stress Terhadap Siklus Menstruasi Pada Mahasiswi D III Kebidanan Stikes Hamzar Lombok Timur - Husniyati Sajalia; R Supini; Arlina Arlina (Journal of Pharmaceutical and Health Research, 2022)
Background: Menstruation is bleeding from the uterus that occurs periodically and cyclically, this is due to the release (desquamation) of the endometrium due to a decrease in ovarian hormones (estrogen and progesterone), especially progesterone, at the end of the ovarian cycle, usually starting about 14 days after ovulation. Stress is known as a causal factor (etiology) of menstrual cycle disorders. Objective: To determine the effect of stress on the menstrual cycle in D III Midwifery students at STIKes Hamzar, East Lombok. Methods: Descriptive observation research method with a cross sectional approach. Samples were 69 people consisting of Level I, Level II and Level III with the sampling technique of total sampling. The instrument used was the Perceived Stress Scale (PSS-10) questionnaire and analyzed by Spearman Rank .Results: The results of this study indicate that there is an effect of stress levels on the menstrual cycle in D III Midwifery students of STIKes Hamzar East Lombok with p-value 0.004 <0.05. Conclusion: There is an effect of stress level on the menstrual cycle in D III Midwifery student at STIKes Hamzar, East Lombok